Analysis of Constitutional Court Decision No.23/PUU-XIX/2021: Legal Efforts for Cassation in Postponing Debt Payment Obligations (PKPU) by Rejecting a Peace Offer from the Debtor - Andaresta, Catherine Putri; Tamy Desindira, Fadhilah Rahmi; Suryanti, Nyulistiowati; Yuanitasari, Deviana (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2023)
Abstract: Developments in the economic and trade sectors are increasingly rapid as well as debt and receivable problems that cannot be resolved by the Bankruptcy Law, the government has made changes to these regulations to become Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. PKPU is an effort used by both debtors and creditors in the event that the debtor considers that he is or is expected to be unable to continue paying his debts that are due and payable, in order to achieve a peace plan for the debtor and creditor. The absence of legal action against a PKPU decision can be a mode or abuse for creditors to reject the peace plan proposed by the debtor so that the debtor is immediately declared bankrupt. In the UUKPKPU it is explained that the peace plan submitted by the debtor in the PKPU is determined based on approval or voting from the creditors. Through a normative juridical approach with analytical descriptive methods, it can be seen to what extent judges apply the principle of balance in deciding a decision and the results of a decision can influence the position of the law.Keywords: PKPU, Bankrupt, Legal Review Abstrak :Perkembangan dalam bidang perekonomian dan perdagangan yang semakin pesat serta permasalahan utang piutang yang belum bisa diselesaikan oleh UU Kepailitan, pemerintah melakukan perubahan terhadap peraturan tersebut menjadi Undang-Undang Nomor 37 Tahun 2004 tentang Kepailitan dan Penundaan Kewajiban Pembayaran Utang. PKPU adalah suatu upaya yang digunakan baik oleh debitur maupun kreditur dalam hal debitur menilai sudah atau diperkirakan tidak dapat melanjutkan pembayaran utang-utangnya yang telah jatuh waktu tempo dan dapat ditagih, agar tercapainya rencana perdamaian bagi debitur dan kreditur. Tidak adanya upaya hukum terhadap putusan PKPU dapat menjadi suatu modus atau penyalahgunaan bagi kreditur untuk menolak rencana perdamaian yang diajukan oleh debitur sehingga debitur langsung dinyatakan pailit. Dalam UUKPKPU dijelaskan bahwa rencana perdamaian yang diajukan oleh debitur dalam PKPU ditentukan berdasarkan persetujuan atau pemungutan suara dari pihak kreditur. Melalui pendekatan Yuridis normatif dengan metode deskriptif analitis dapat ditinjau sejauh mana hakim menerapkan asas keseimbangan dalam memutus suatu putusan dan hasil dari suatu putusan dapat mempengaruhi kedudukan Undang-undang. Kata kunci : PKPU, Pailit, Pengujian Undang-undang